Synaptic Loss in Multiple Sclerosis Spinal Cord. Issue 3 (16th July 2020) - Petrova, Natalia; Nutma, Erik; Carassiti, Daniele; RS Newman, James; Amor, Sandra; Altmann, Daniel R.; Baker, David; Schmierer, Klaus
Abstract : Disability in multiple sclerosis (MS) is considered primarily a result of axonal loss. However, correlation with spinal cord cross‐sectional area—a predictor of disability—is poor, questioning the unique role of axonal loss. We investigated the degree of synaptic loss in postmortem spinal cords (18 chronic MS, 8 healthy controls) using immunohistochemistry for synaptophysin and synapsin. Substantial (58–96%) loss of synapses throughout the spinal cord was detected, along with moderate (47%) loss of anterior horn neurons, notably in demyelinating MS lesions. We conclude that synaptic loss is significant in chronic MS, likely contributing to disability accrual. ANN NEUROL 2020;88:619–625